PERBANDINGAN JENIS MEDIA TANAM TANAH ENTISOL YANG TERPAPAR SATU KALI DAN DUA KALI OLEH LIMBAH CAIR NANAS TERHADAP PERTUMBUHAN SELEDRI (Apium graveolens L.) SEBAGAI SUMBER BELAJAR BIOLOGI - Kartika Sari, Irma Yunita Sari (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
Abstract. This research to know effect of Pineapple Liquid Compost (PLC) in long term the growth of celery. This research conducted at the village in Yosodadi 21 Polos, East Metro, Metro City since 7 December until 28 February 2015. This research is experimental research, the design used the Complete Random Design (CRD). This research used entisol soil that was exposed by PLC once and entisol soil that was exposed by PLC twice. The treatment was done to them both by giving PLC about 200ml in a time per three days. The data analysis was done by using normality test (liliefors), homogeneity test (barlett) and Ttes. It shows that there is no negative effect of fertilizer use PLC in the long term against the growth of celery in entisol soil that was exposed by PLC once and entisol soil that was exposed by PLC twice.Â